Aljabar: Bagaimana Kemampuan Pemahaman Matematis Siswa Kelas VII? - Ali Noeruddin; Piyanto Piyanto (IKIP PGRI Bojonegoro, 2021)
Abstract: A learning process, understanding is a prerequisite for improving cognitive abilities. To find out the extent of students' mathematical understanding ability by describing based on indicators used by researchers. The purpose of this study was to describe the five abilities of students towards mathematical understanding of algebra material in grade 7 MTs. This research method is a qualitative descriptive study. The sample selection uses the purposive sample method, namely three 7th grade students at MTs Manbaul Islam Soko, Tuban Regency. The research instrument used was a UAS test and interview questions, while to ensure the validity of the data, the researcher analyzed the data in two ways, namely the triangulation of data sources and triangulation of methods. The results of the study describe five students' mathematical understanding abilities on algebra material, namely reasoning and argument, devising strategies for solving problems, mathematizing, and communication. Keywords: Mathematical understanding ability, algebra Abstrak: Suatu proses belajar, pemahaman merupakan prasyarat untuk meningkatkan kemampuan kognitif. Untuk mengetahui sejauh manakah kemampuan pemahaman matematis siswa dengan menguraikan berdasarkan indikator yang digunakan peneliti. Tujuan penelitian ini adalah untuk mendeskripsikan lima kemampuan siswa terhadap pemahaman matematis pada materi aljabar di kelas 7 MTs. Metode penelitian ini adalah penelitian deskriptif kualitatif. Pemilihan sampel menggunakan metodhe sampel bertujuan (Purposive Sample) yaitu tiga siswa kelas 7 di MTs Manbaul Islam Soko Kabupaten Tuban. Instrumen penelitian yang digunakan adalah tes soal UAS dan wawancara, sedangkan untuk memastikan kevalidan data, peneliti menganalisis data dengan dua cara yaitu triangulasi sumber data dan triangulasi metode. Hasil penelitian memaparkan lima kemampuan pemahaman matematis siswa pada materi aljabar yaitu reasoning and argument, devising strategies for solving problems, mathematizing, dan communication. Kata Kunci: kemampuan pemahaman matematis, aljabar